Representation of Military Barack Policy for Problem-Ful Students in Online Media Reporting - Finessa Salsabila; Untung Yuwono (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to examine how Indonesian online media represent the military camp policy for problematic students initiated by Dedi Mulyadi. The research employs a qualitative approach using Van Dijk’s critical discourse analysis model combined with intratextuality and appraisal theory. The data consist of five online news articles published by Metrotvnews, Okezone, Tempo, Tribunnews, and Viva.co.id between May 8–9, 2025. The analysis covers three levels of discourse structure: macrostructure, superstructure, and microstructure. The findings reveal that four of the five media outlets frame the military camp policy positively by emphasizing character building, legality, and human resource development, while Tribunnews presents a more critical stance by highlighting possible human rights issues and the decline of democratic values. The analysis also shows that media attitudes are represented through cohesive text structures and evaluative language that reinforce either support or opposition to the policy. These findings indicate that the media actively shape public perspectives on educational policy through strategies of representation, attitude, and framing in their news discourse